Evaluation of the ion trap MS performance for quantification of flavonoids and comparison to UV detection - Stanoeva, Jasmina Petreska; Stefova, Marina (Wiley, 2012)
The application of an ion trap mass spectrometer, usually employed for identification, has been here systematically evaluated for quantitative analysis of various conjugated forms of flavonoids and compared with UV quantification. Three MS methods were tested to assess the potential and limits of the ion trap for quantification of flavonoids: full-scan experiment MS(2) , isolated ion experiment MS, and full-scan experiment MS. The test was performed using nine reference standards of flavonoids with six different aglycones: luteolin, apigenin, hypolaetin, 4'-O-methylhypolaetin, isoscutellarein and 4'-O-methylisoscutellarein in the form of 7-O-glucosides and diglucosides, mono or diacetylated, isolated from Sideritis scardica. The analytical characteristics of the tested MS methods were shown to be comparable to UV with regards to precision and accuracy, and superior for selectivity and sensitivity especially when using extracted ion chromatograms. Detection limits did not differ significantly between the MS methods but were significantly lower than those obtained with UV detection by one order of magnitude. Another issue addressed by these results was the choice of most suitable standard substances for quantification of flavonoids with various substituents attached when using MS. In UV detection, the nature of the aglycone is crucial for the absorbance properties, and various derivatives can be quantified with the available one with the same aglycone. Here, it was shown that in MS detection, one flavone derivative can be quantified using other available derivatives with similar substitution pattern with regards to attached and acetylated sugars, whereas the nature of the aglycone is not crucial.